Educate in the digital age: teaching-learning processes with digital natives - Santos, Vanessa Zucco dos; Borba, Eduardo Zilles; Reszka, Maria de Fátima (Cadernos de Educação Tecnologia e Sociedade, 2021)
The integration of digital technologies with educational practices has been generating debates and questions about the reconfigurations in the teaching and learning process. In fact, the experiences mediated by teachers through devices and technological media stimulate new forms of interaction in the classroom. Anastasiou and Alves (2015), Moran (2015) or Bates (2016) indicate that pedagogical practices in the digital age cause transformations in students and teachers, as they encourage horizontal dialogues, proactivity, cooperation and collective protagonists, which can be understood as teaching-learning process. This article presents a discussion about education in the digital age based on these teaching-learning processes. It is presented a theoretical review followed by an empirical study through an exploratory approach involving participant observations, focus groups and interviews with students and teachers of an Early Childhood and Elementary Education at a municipal school located in Novo Hamburgo, RS (Brazil), which is characterized by encouraging the integration of digital technologies in the classroom. Results point out that teachers and students are adapting to teaching-learning processes, especially through hybrid moments, when digital tools optimize the construction of knowledge in the face-to-face education.